PRAKTIK PENGGILINGAN DAGING DI PASAR ANGSO DUO BARU KOTA JAMBI DENGAN PENDEKATAN SISTEM JAMINAN HALAL - Heni Pratiwi (International Journal Mathla’ul Anwar of Halal Issues, 2025)
Halal is a primary requirement for Muslim consumers when consuming food products. A halal assurance system is a mechanism that producers must implement if they wish to apply for halal certification from BPJPH (Halal Product Assurance Agency). The current problem faced by small and medium enterprises in the Angso Duo market is the lack of halal certification from BPJPH. Manshurin 354 Meat Grinding is a meat grinding production house that grinds chicken and beef. The second partner is Manshurin 354 Meatball Printing, a business unit that produces meatball printing. This activity aims to fulfill the assignment for the halal product management course and to determine whether the store has obtained halal certification. The result of this activity is awareness among partner business units to implement the halal assurance system in their businesses. Suggestions for the sustainability of the program include comprehensive outreach to food product trader associations and producers regarding the importance of halal certification and collaboration between academics and halal certification institutions regarding halal certificate management.